A imagem do tempo suspenso: eco-logia e ecologia nos processos de criação de webvídeos - Wodevotzky, Robson Kumode (2021)
This thesis proposes to analyze the communication environment created by the webvideos, audiovisual produced specifically to/on the web, with the aim of investigating how the abstractions of spatiality and corporeality on the web change the ways of binding and build a new time image, a suspended time, and how this image reverberates in the creation processes of the webvideos. Therefore, the research corpus is composed by webvideos of the producers Felipe Neto, Kéfera Buchmann and Whindersson Nunes and by the platforms Youtube, Instagram and Tik Tok. These producers have become public figures in Brazil since the second decade of the current century and their content is released in the selected platforms. The research starts from the hypothesis that these audiovisuals have time strategies that reverberate the environmental temporality and seek to apprehend the interactors, abstracting their bodies and surrounding spatiality and, thereby, feeding back and sustaining the suspended time image in the creation processes of emptied images and in echo; on the other hand, these processes may be ecological, retrieving the image genealogy from the reconstruction in repetition of these images and their environments. The corpus will be analysed in order to investigate the dynamics of the platforms and elements used in the making of the webvideos that can potentially impact the temporal relations of this environment. The primal theoretical-methodological basis consists of Norval Baitello Junior’s work, with his image theory; Vilém Flusser, regarding the escalation of abstraction; Norbert Elias and Hans Blumenberg, about the time; Vicente Romano, in its elaboration of a communication ecology; Sören Kierkegaard, with the repetition concept; and Lucia Leão e Eugênio Trivinho, with their works about cyberculture